Background noise estimation of the geomagnetic signal - X. Yao; S. Zhang; Y. Teng; D. Yang (Geoscientific Instrumentation, Methods and Data Systems, 2018)
A fast Fourier transform was applied to fit the geomagnetic diurnal variation. Fitting results showed that when the polynomial degree was greater than 160, the residual error was close to 0 nT. White noise is the main component of the residual error when the polynomial degree was greater than 160, so this method was adopted to calculate the background noise of the geomagnetic field. Spectrum analysis further demonstrated that the noise estimation result is reliable.